DESIGN AND DEVELOPMENT OF MORSE LEARNING SYSTEM APPLICATION BASED ON VISUAL BASIC - Bayu Wibisono; Alexander Victor Bukit; Adi Bandono; Edy Widodo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
School of Communication (Sekom) is a place for educational institutions of the Indonesian Navy'sNational Army which has the duty to educate and prepare human resources in the field of communication.In providing Morse gesture learning material, the instructors still use the media in the form of a Morseknock tool manually, the news is received and recorded by other students with a sheet of paper or abook. There are ideas or ideas from the author to combine the Morse signal method using computermedia in its implementation. The design of this study was carried out to provide an overview of thesystem to be created. The flow of news delivery is news that is processed in the server and then sentusing the computer as a server automatically so that it will come out in the form of morse audio after theprocess begins and then is received by students using a computer as a client and the results of studentanswers will be automatically saved into the server, after saving the teacher can retrieve the resultsdirectly typing students who automatically have a value that is managed in the server. The assessmentsystem is automatically processed in the server by means of a comparison between the news sent by theteacher with the results typed by students.Keywords: Morse, Server and client.